1996
DOI: 10.1021/ja960525k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Hydrolysis of Aflatoxin B1 exo-8,9-Epoxide and Rearrangement of the Dihydrodiol

Abstract: Aflatoxin B1 (AFB1) is thought to play a large role in human liver cancer in some parts of the world, and the mechanism of genotoxicity is generally considered to involve the DNA adduct formed at the guanyl N7 atom. The exo epoxide, the genotoxic isomer formed by human cytochrome P450 3A4, has been known to be very unstable in H2O (t 1/2 < 10 s). The rates of hydrolysis of AFB1 exo epoxide have been determined as a function of pH using stopped flow kinetics. The spontaneous reaction with solvent is faster than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 34 publications
5
103
0
Order By: Relevance
“…Although we did not measure the expression of GSTs in this particular study, previous studies have demonstrated that the level of GSTs in these cells are negligible (20). In the case of AFB 1 dihydrodiol, this metabolite can undergo a slow, base-catalyzed ring opening to a dialdehyde (7,31) that is capable of forming Schiff base adducts with protein amino groups, particularly lysine (16). Previous studies suggest that this type of reaction could be involved in the acute toxicity of AFB 1 (12).…”
Section: Discussionmentioning
confidence: 87%
“…Although we did not measure the expression of GSTs in this particular study, previous studies have demonstrated that the level of GSTs in these cells are negligible (20). In the case of AFB 1 dihydrodiol, this metabolite can undergo a slow, base-catalyzed ring opening to a dialdehyde (7,31) that is capable of forming Schiff base adducts with protein amino groups, particularly lysine (16). Previous studies suggest that this type of reaction could be involved in the acute toxicity of AFB 1 (12).…”
Section: Discussionmentioning
confidence: 87%
“…AFB 1 is oxidized by cytochrome P450s to yield a variety of metabolites, and its toxicology has been reviewed (4). The major reactive metabolite is the exo-AFB 1 8,9-epoxide, which if not detoxified, can bind to double-stranded DNA to form the promutagenic AFB 1 -N 7 -guanine adduct or, following hydrolysis to the AFB 1 -dihydrodiol, with proteins such as albumin (5)(6)(7)(8). Both urinary AFB 1 -N 7 -guanine and serum AF-albumin levels are correlated with dietary intake of AFs (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic activation of AFB 1 by the cytochrome P450 system generates a highly reactive intermediate, AFB 1 -8,9-epoxide, capable of covalent binding to DNA (Essigman et al, 1982;Eaton and Gallagher, 1994;Johnson et al, 1996). The principal adduct formed is 8, 9 -dihydro -8 -(N7 -guanyl) -9 -hydroxya¯atoxin B 1 (AFB 1 -N7-Gua), both in vitro (Essigman et al, 1977) and in vivo (Lin et al, 1977;Croy et al, 1978).…”
Section: Introductionmentioning
confidence: 99%